2012
DOI: 10.4236/jmmce.2012.116043
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of New Non Linear Optical Bis-Glycine Hydro Bromide (BGHB) Single Crystal

Abstract: A new non linear optical material, Bis-Glycine Hydro bromide (BGHB), has been synthesized. Single crystals of BGHB have been grown successfully by slow evaporation method. The solubility of the material was measured in various solvents such as ethanol, acetone and water. It was found to have extremely low solubility in ethanol and acetone. The grown crystals were characterized by recording the powder diffraction and identifying the diffracting planes. Using single crystal diffractometer the morphology of BGHB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Hence, it is confirmed that the material has NLO efficiency of about 1.5 times that of the KDP crystal. The nonlinear optical study confirms the SHG property of the material equal to 1.5 times that of the standard KDP and this prediction is comparable with the reported value of 1.25 [20].…”
Section: Nlo Test: Kurtzsupporting
confidence: 89%
“…Hence, it is confirmed that the material has NLO efficiency of about 1.5 times that of the KDP crystal. The nonlinear optical study confirms the SHG property of the material equal to 1.5 times that of the standard KDP and this prediction is comparable with the reported value of 1.25 [20].…”
Section: Nlo Test: Kurtzsupporting
confidence: 89%
“…Sampathkrishnan et al 18 determined the crystal structure of BGHB [(C2H5NO2)2 Hbr] which is non-centro symmetric space group P212121, with the cell dimension a = 5.39 Å, b = 8.18 Å, c = 18.39 Å, α = 90.18 Å, β = 89.88 Å, γ = 89.99 °V = 812.43. The optimized geometrical parameters (bond lengths and angels) by DFT, B3LYP with 6.311 ++G(d,p) as basis set are listed in Table-2.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids and their complexes are the organic or semi-organic materials that have attracted great attention due to their ability in ease of processing in the assembly of optical devices. The complete understanding of the optical properties of amino acid crystals, as well as other organic crystals, still requires more attention [1][2][3][4][5][6][7]. 3-Aminopropionic acid is commonly known as β-alanine with molecular formula C3H7NO2 and in which the amino group is at the β-position from the carboxylate group [8][9][10].…”
Section: Introductionmentioning
confidence: 99%